Energy Consumption Studies of Machine-Tractor Aggregate for Staggered Sowing of Hoeing Crops on Calcic Chernozem - Beloev Hristo; Dimitrov Petar; Kangalov Plamen; Stoyanov Kaloyan; Atanasov Atanas; Enchev Evgeni; Donev Vlado (Acta Technologica Agriculturae)
In the Republic of Bulgaria, in the last few years, a DeltaRow technology of staggered sowing of the seeds of hoeing crops such as maize for grain and sunflower has been successfully applied in some agricultural regions. An Azurit 10.8 seed drill is used to implement the staggered sowing technology. This precision seeder is aggregated with tractors with a nominal towing resistance of 30 kN (New Holland T6.165). The efficient use of this machine-tractor aggregate required a comprehensive study of its energy consumption by applying the tensiometer method. This paper discusses the scheme of the main procedures of the experiment conducted, the order and method of determining the relevant energy indicators, and the results of this study. The findings demonstrate that the chosen energy source in the newly assembled machine-tractor unit is appropriately chosen due to its towing and power capabilities because the maximum towing resistance, when sowing a field after pre-sowing treatment, reaches up to 12.1 kN, while the nominal one of this tractor is 30 kN. In addition, its maximum power consumption reaches up to 56.98 kW, with an engine load factor of 53.25% and acceptable wheelspin of up to 6.3% in the operating speed range of 2.3–3.4 m·s−1. In addition, the researched machine-tractor aggregate in terms of energy consumption ensures an optimum towing and speed of operation when carrying out the technological operation of staggered sowing with paired sown rows of hoeing crops on the agricultural lands of the Republic of Bulgaria with calcic chernozem.